Necesidades básicas de los cuidadores primarios de niños con cáncer - Carrasco Ubidia, Estefanía Andrea (2013)
The family is a system which throughout its existence faces various situations and goes through several changes. When it comes to a child's disease, such as cancer, all members of this system experience new realities and begin to live a new stage. The parents, especially the mother is the one who becomes the primary caregiver of the sick relative, accompanying him or her all the time and giving all their support and care. Therefore, the objective of this study is to: recognize the perception of primary caregivers of children with cancer about their basic needs during the diagnostic-treatment process. In terms of specific objectives; to identify instrumental needs of primary caregivers; to determine support needs; and, to establish which needs are covered by the hospital. For this purpose we worked with 50 primary caregivers, 15 of children in hospital and 35 of children on outpatient treatment of a children's hospital in the city of Quito, using a descriptive-exploratory-quantitative method, study that was carried out in order to explore the main needs of primary caregivers of children with cancer when they are going through the process of the disease, then we proceeded to describe the needs. The main results of this study showed that the primary caregiver of a child with cancer during the diagnosis and treatment process is the mother; the greatest need is for them economic; and, emotional support is critical because when the child is diagnosed they go through several and severe emotional changes. As for the main findings, it was determined that primary caregivers are key in the process of their child's illness, the whole family goes through these changes and needs, and therefore need help from a professional. The study was based on systemic family therapy, as the entire family system is involved in the process.